Le bizarre ordinaire - Régine Borderie (Flaubert: Revue Critique et Génétique)
The article focuses on the bizarre as variegation in L’Éducation sentimentale, i.e. the ordinary but various or even disparate associations or series of things, thoughts, facts etc. It studies the figures of variegation and its stakes: it contributes to the representation of reality or life, to its criticism on a comic mode, and to the expression of a pessimistic vision of existence.